Sex-specific non-linear associations between body mass index and impaired pulmonary ventilation function in a community-based population: Longgang COPD study - Huang, Hao; Huang, Xueliang; Liao, Jiaman; Li, Yushao; Su, Yaoting; Meng, Yaxian; Zhan, Yiqiang (Frontiers in Pharmacology, 2023)
Aim: To investigate the prevalence of impaired pulmonary ventilation function and its association with body mass index (BMI) in a community-based population in Shenzhen, China. Methods: Study participants were recruited from Nanlian Community in Shenzhen, China, and spirometry was performed to assess lung function including forced volume capacity (FVC), forced expiratory volume in 1 second (FEV1), FEV1/FVC ratio, and FEV1 divided by predicted value. Impaired pulmonary ventilation function was determined by the Chinese Guideline of Pulmonary Function Examination. Multivariable logistic regression models were used to examine the association between BMI and impaired pulmonary ventilation function. Age, sex, educational attainment, occupation, and current cigarette smoking were used as potential confounders. Results: Of the 1206 participants, 612 (50.8%) were men and 594 (49.3%) were women with the average age being 53.7 years old. After adjusting for age, sex, educational attainment, occupation, and current cigarette smoking, higher BMI was associated with lower odds (odds ratio: 0.98, 95% confidence interval: 0.97, 0.99) of impaired pulmonary ventilation function by assuming a linear relationship. Further investigation of the interaction terms, we found that the magnitudes of the associations differed in men and women. A U-shaped relationship was observed in women, while the association was almost linear in men. Conclusions: The relationship between BMI and impaired pulmonary ventilation function was U-shaped in women and linear in men.